UPAYA MENINGKATKAN MINAT DAN HASIL BELAJAR MATEMATIKA MELALUI MODEL PEMBELAJARAN LEARNING CYCLE SISWA KELAS IV SD NEGERI SIYONO III - Rizka Diah Amalia; Istiqomah Istiqomah (Universitas Sarjanawiyata Tamansiswa, 2020)
The objective of this research is to describe the process of Learning Cycle to improve the students’ effort and math learning outcomes in IV grade SD Negeri Siyono III. The action hypothesis used in this research was the Learning Cycle model could improve the students’ effort and math learning outcomes in IV grade of SD Negeri Siyono III. The method used in this research is Classroom Action Research (CAR). The subject of this research was 19 students of IV grade SD Negeri Siyono III. The object of this research was the effort and students’ math learning outcomes from the whole learning process. The data were collected by using the observation sheet, documentation, and test. The resulting finding of the study implies that after the implementation of the Learning Cycle model, the student's effort and math learning outcomes were improved. The result of the study showed that there is a significant improvement in effort aspect mean score from pre-cycle to the cycle I, that is 49,34% to 66,45%. From cycle I to cycle II that is 66,45% to 74,34%. The mean of student's math learning outcomes improved from the pre-cycle that is 51.10 to cycle I that is 62,42 and cycle II that is 73,74. Classical completeness percentage was improved from 10,53% in in the pre-cycle to 47,37% in the cycle I, and 78,95% in the cycle II. By using the Learning Cycle model can improve the students’ effort and math learning outcomes, hopefully, the school can using the Learning Cycle model in their teaching-learning activity.